Education on the urgency of financial independence for single parent women at the Yayasan Yatim Sahabat Hayatni in the Tangerang and Cipondoh areas - Muflih Adi Laksono (Universitas Muhammadiyah Magelang, 2023)
The aim of this community service is to increase knowledge about financial independence for single parent women at the Yayasan Yatim Sahabat Hatayni in the Tangerang and Cipondoh areas. The community service methods used were mentoring and education. Implementation steps included education, questions and answers, personal counseling, evaluation and solutions. The result of the program is that 50 single parent women are able to identify the reasons for not having financial independence. Apart from that, participants can understand the importance of having financial independence with indicators including not having the habit of getting into debt to meet their needs, having financial reserves or emergency money and not being a burden on other people.